Treatment pathways, resource use and costs in the management of small cell lung cancer. Issue 10 (1st October 2001) - Oliver, E; Killen, J; Kiebert, G; Hutton, J; Hall, R; Higgins, B; Bourke, S; Paschen, B
Abstract : BACKGROUND: Small cell lung cancer (SCLC) represents about 20% of primary lung tumours and the costs associated with the management of SCLC can be significant. The main objective of this study was to obtain information on current patterns of care and associated resource use and costs for patients with SCLC from initial diagnosis and treatment phase, throughout disease progression and terminal care. METHODS: A 4 year retrospective patient chart analysis (1994–7) was conducted on a consecutive series of 109 patients diagnosed with SCLC in two Newcastle hospitals. For this consecutive series of patients all details about care received including tests and procedures, treatment, and medication from diagnosis till death were recorded. Pathways of care and forms were designed to enable resource use to be captured for different disease phases. Unit costs were determined from a variety of sources including the Newcastle Hospitals NHS Trust Finance Department and the British National Formulary. RESULTS: The average total cost per patient calculated for the full cohort of 109 patients was £11556. Initial treatment was the most resource use intensive constituting 48.2% of the total cost. The major cost element throughout all disease phases was hospitalisation. Twenty eight percent of the total costs of care occur after recurrence of the disease until death, of which 73% are generated by terminal care. CONCLUSION: The results of this retrospective medical chart analysis show that the costs of care of SCLC are considerable, although the variability between patients in terms of the type and quantity of resource use is very high. Analyses such as this provide a useful insight into resources used in actual clinical practice.